Kajian Atas Kredibilitas Imam Abu Hanifah di Bidang Hadis - Mesra, Alimin (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2011)
This essay affirms that Imam Abu Hanifah was a hadith expert (muhaddits). This thesis is a conclusion from analysis of related data based on hadith criticism approach and conventional paradigm of hadith theory. The variables used as a measure are his individual integrity, known as al-‘adalah (moral integrity) and al-dhabth (intellectual integrity), role in hadith narration process (tahammul wa ada’ al-hadis), contribution in hadith critic and terminology, and elaboration of the criteria of the hadith validity. Based on these variables, this essay finds that Abu Hanifah’s moral and intellectual integrity are recognized by a number of popular hadith critics, such as Ali al-Madini, Sufyan al-Tsauriy, Ibn al-Mubarak ect., and the hadith narrated by him in fact reached a relatively large amount, and that can be seen in the compilations by Abu al-Mu’ayyad al-Khawarizmi, Jami’ al-Masanid, and by Hasan al-Syaibaniy, Kitab al-Atsar. In addition, Abu Hanifah also contributed significantly to the formation and discussion of hadith terminology. His concept of hadis masyhur and of the criteria of the hadith validity has, for an example, inspired the scholars who have come and lived after his period time. This essay, therefore, argues against the views of some scholars who have discredited him in the field of hadith, and who have considered him as jurist only. To sum up, Abu Hanifah deserves to be put in an equivalent position as his counterparts, the other three founders of Islamic law schools, in both Islamic law and hadith; he is an outstanding jurist as well as muhaddith.